Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.12991/mpj.20162036047
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Chrysophyllum albidum and Anacardium occidentale gums as wet and dry binders in ciprofloxacin tablets

Abstract: This study aimed to extract gums from Chrysophyllum albidum (CAG) fruit and Anacardium occidentale (AOG) bark tears; and characterize them as wet and dry binders in tablets. AOG and CAG were extracted using old and modified protocols respectively. CAG, polyvinylpyrrolidone (PVP) and gelatin (GTN) were used in wet granulation (wG), while CAG, AOG, pregelatinized starch (PGS) and hydroxypropylmethyl cellulose (HPMC) were used in direct compression (dC). Granules and powder blends were evaluated for flowability, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The gum was thereafter dried and ground to fine powder for storage. Okoye and Ndiwe (2016) compared the quantity of gum obtained from the solution of the exocarp and mesocarp and that of the mesocarp alone while also comparing the effect of solvent used on the amount of gum precipitated from both the exocarp and mesocarp and mesocarp alone. The yield of the gum from the exocarp and mesocarp together was lower to that obtained from the mesocarp alone.…”
Section: Adekanmi Dg Olowofoyeku Aementioning
confidence: 99%
See 1 more Smart Citation
“…The gum was thereafter dried and ground to fine powder for storage. Okoye and Ndiwe (2016) compared the quantity of gum obtained from the solution of the exocarp and mesocarp and that of the mesocarp alone while also comparing the effect of solvent used on the amount of gum precipitated from both the exocarp and mesocarp and mesocarp alone. The yield of the gum from the exocarp and mesocarp together was lower to that obtained from the mesocarp alone.…”
Section: Adekanmi Dg Olowofoyeku Aementioning
confidence: 99%
“…A similar study by Okoye and Ndiwe (2016) compared the performance of the pulp gum and cashew gum as binder on ciprofloxacin tablets. The study revealed that the gums are viable binders in pharmaceutical applications but the mechanical properties of the tablets were only comparable at 6% and 2% concentration respectively.…”
Section: Adekanmi Dg Olowofoyeku Aementioning
confidence: 99%
“…{African star apple (ASA)} is an angiosperm in the Sapotaceae family and Ebernales order (Ibrahim et al, 2017). When unripe, the fruit is dark green, but as it ripens, it turns a yellowishorange tint, and when overripe, it turns into rusty orange color (Okoye and Ndiwe, 2016). C. albidum fruit has a high economic value due to its many industrial, medical, and food applications (Abolaji and Adiaha, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the widespread eating of this wild fruit and its significant contribution to Nigerians' nutritional intake, the palatability of fresh C. albidum fruits can only last a few days before it loses its aroma, color, flavor, and appearance (Iro and Ezejindu, 2017). During the ripening season of the fruit, poor storage of C. albidum fruits frequently results in a lot of waste (Okoye and Ndiwe, 2016). The browning in the head region (stem end) of C. albidum fruits could extend into the edible pulp, resulting in a loss of firmness and bursting of the fruits (Sunmonu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The gum extracted from the fruit had been characterized and used as binder and suspending agent. [12][13][14][15][16] In this present work, the effect of drug-polymer ratio on the mechanical properties and release profile of ciprofloxacin tablets using Chrysophyllum albidum gum, xanthan gum and HPMC (hydroxypropylmethylcellulose) of varied ratio was studied.…”
Section: Introductionmentioning
confidence: 99%